Role of community pharmacy and pharmacists in self care in Sweden - Tommy Westerlund; Lars-Åke Söderlund (Exploratory Research in Clinical and Social Pharmacy, 2023)
Background: Self care is an important concept, which is increasingly being applied by policy makers on a large scale. It is associated with improved health literacy and technological advances. Community pharmacy practitioners are easily accessible for self care counselling, purchase of non-prescription products and for referrals to other healthcare providers. Objective: To describe self care policies and strategies in Swedish healthcare authorities, pharmaceutical organizations and community pharmacy. Methods: A search was conducted to retrieve self care policy documents and strategies in Swedish healthcare authorities, pharmaceutical organizations and community pharmacy on respective websites, as well as personal contacts with key persons in pharmaceutical organizations and community pharmacy practice. Results: A new law on self care was adopted by the Swedish Parliament becoming effective in 2023. The law defines self care as a healthcare measure that has been assessed by a treating licenced healthcare practitioner to be possible to be performed by the patient him/herself. The law includes a wide range of measures. According to a Government Commission that followed Sweden's the National Pharmaceutical Strategy's Action Plan in 2018, the Medical Products Agency (MPA) was assigned to establish requirements of qualifications in self care counselling. In its report in late 2022, the MPA stated that self care counselling by community pharmacy practitioners plays an important role in society. The new requirements are expected to become effective in mid-2023. None of the four community pharmacy chains operating 97% of Sweden's community pharmacies have developed any specific self care policies, although self care counselling and sales of non-prescription products, as well as provision of some primary healthcare services, constitute important components of their operations. Furthermore, all Swedish pharmacies offer several digital self care solutions, supporting people to manage their own health. Neither the Swedish Pharmacy Association, representing most pharmacies, nor the Swedish Pharmacists Association, the trade union, have developed any self care policies. However, the Swedish Association of the Pharmaceutical Industry is promulgating Swedish self care reform using a systematic review of self care and which medicines should be over-the-counter. Conclusions: Self care is not currently established as a core pillar of a Swedish national health strategy. There are further opportunities to enable pharmacists to fulfil their potential in supporting individual wellbeing and promoting self care interventions. A new system needs to be created which fully integrates the promotion of everyday wellbeing, self care for self-treatable conditions and the management of long-term conditions.